Adjusting advance care planning to older people's needs: results from focus groups and interviews - Heike Gerger; Anneke van Dijk-de Vries; Albine Moser; Inge Jochem; Marja Veenstra; Marieke Perry; Marloes van Bokhoven (BMC, 2024)
Abstract Background Advance care planning (ACP) is becoming increasingly important in medical care. Some suggest standardized approaches to initiate ACP with all older adults. However, the idea of patient-centered care suggests more nuanced approaches tailored to individual older adults' needs. This study investigated how older adults with different views and needs about ACP can be approached in an adequate and most beneficial way by health care professionals. Methods We used questionnaires, interviews, focus groups and informal conversations with older adults, living in their own homes, who volunteered to take part in our research. The research was participatory as we collaborated closely with practice partners and we used the obtained findings immediately and continuously to inform the next steps of our research throughout the process. Results We identified three subgroups of older adults with differential needs regarding ACP-related activities: The first group avoids talking about their needs and wishes for care towards the end of life. These older people benefit from activities, which aim at motivating them to concern themselves with ACP-related topics. The second group consists of older adults who are in principle open for ACP-conversations but do not initiate these themselves. This group either trusts their next-of-kin or their healthcare professional to act in accordance with their wishes or does not bring up the topic in order to avoid confronting relevant others with possibly unpleasant topics. This group of people benefits from information about ACP and from healthcare professionals initiating the ACP process. The third group of older people initiates the ACP process themselves, gathers information, and takes the necessary steps for ACP. With this group it remains relevant to check carefully whether they have indeed taken all relevant steps and shared the information with all relevant involved care institutions and relatives. Conclusions We propose a model to simplify adjustments of ACP to individuals' needs. Our suggested approach might contribute to increasing the motivation of older people to engage in ACP conversations if these are more closely related to their own needs. Further, it might also contribute to simplifying the individual shaping of the ACP process for healthcare professionals as our suggested model offers clear guidance for approaching different types of older people in different ways. The suggested approach may in future be used for training health care professionals in the conduct of ACP conversations.